Seismic performance of nonrectangular RC walls with limited transverse reinforcement - Wang, Chenghong (2013)
Nonrectangular Reinforced Concrete (RC) walls especially those with L- and T-shaped cross section are commonly adopted in constructions and buildings; and these wall systems in moderate seismic hazard regions like Singapore are generally designed with limited transverse reinforcement.